(untitled) (Research, Society and Development, 2021)
The minimally invasive ceramic laminates popularly known as "contact lenses" are thin layers of porcelain that cover the buccal surface of the anterior teeth in order to modify their size, shape and color. They are becoming more and more popular due to their enormous dissemination of beautiful results in different media, but mainly because they have a more conservative execution protocol, with less aggression to dental tissues than traditional facets. Thus, the objective of this work was to evaluate the causes of failures that culminate in the retreatment of aesthetic restorations of minimally invasive ceramic veneers and how the literature guides the clinical management in this situation. For that, an integrative literature review was carried out. Studies that are relevant and relevant with the proposed title will be selected: Retreatment in minimally invasive ceramic laminates. Selecting complete studies, in Portuguese and English, depending on the data platform, that addressed or studied the topic in question. Including articles that dealt with this topic in the research, however, academic documents were not selected for this review that presented in the summary a distance from the researched topic or that presented conflicts of interest.